Effects of diverse food processing conditions on the structure and solubility of wheat, barley and rye endosperm dietary fibre. (January 2016) - Comino, Penny; Collins, Helen; Lahnstein, Jelle; Gidley, Michael J.
Abstract: The effects of archetypal food processing conditions (dough formation, baking, extrusion, and cooking/boiling) on dietary fibre structure and extractability from the endosperm flours of rye, hull less barley and wheat are reported. For all flours and processes, the distributions of soluble/insoluble cell wall dietary fibre as well as the chemical composition (arabinoxylan (AX) branching patterns, β-glucan DP3/DP4 (DP = degree of polymerisation) ratios) of solubilised fractions were characterised. The results show that overall the total amounts of AX and β-glucan (BG) were not significantly affected by processing but that there were similar increases in the soluble fibre fraction (20–29%) for baked, extruded, and boiled/cooked processes for each flour, with lower (10–15%) increases for all flours processed into dough. In all cases, solubilised fractions of AX and BG had very similar chemical structures to the starting flour, suggesting that increased solubilisation was not due to specific chemical fractions. Confocal images illustrate loosely-held associations of β-glucan with the cell walls of processed foods in contrast to some of the arabinoxylans which appear more tightly held within the residual cell walls. The similarities in behaviour across the three grains are consistent with mechanical treatments during food preparation resulting in similar extents of disentanglement of physically-constrained AX and BG leading to their partial solubilisation. Highlights: Effects of four food processing conditions on each of three cereal flours studied. Structure and yield of soluble/insoluble dietary fibre determined for all treatments. Consistent increase in soluble fibre yields across three flours after each treatment. Polysaccharide chemical structure very similar for soluble and insoluble fractions. Diverse food treatments increase fibre solubility through a common mechanism.